Correlation between agility and jumping in young soccer players. (Revista horizonte, 2014)
The aim of the study was to correlate agility and jump performance in young soccer players. A group of 38 male athletes were assessed (age 10,9 Â± 2,5 y). A soccer-specific agility test (â€œMeylanâ€ test), theÂ bilateral countermovement jump (CMJ) test and the unilateral CMJ test (with both, left and right leg) were used to assess the athletes. A significant correlation was observed between agility and CMJ bilateral (r = -0.55, p